Cell-directed aptamer therapeutic targeting for cancers including those within the central nervous system. (31st December 2022) - Wei, Jun; Song, Renduo; Sabbagh, Aria; Marisetty, Anantha; Shukla, Neal; Fang, Dexing; Najem, Hinda; Ott, Martina; Long, James; Zhai, Lijie; Lesniak, Maciej S.; James, Charles David; et al.
ABSTRACT: Osteopontin (OPN) is produced by tumor cells as well as by myeloid cells and is enriched in the tumor microenvironment (TME) of many cancers. Given the roles of OPN in tumor progression and immune suppression, we hypothesized that targeting OPN with aptamers that have high affinity and specificity could be a promising therapeutic strategy. Bi-specific aptamers targeting ligands for cellular internalization were conjugated to siRNAs to suppress OPN were created, and therapeutic leads were selected based on target engagement and in vivo activity. Aptamers as carriers for siRNA approaches were created including a cancer targeting nucleolin aptamer Ncl-OPN siRNA and a myeloid targeting CpG oligodeoxynucleotide (ODN)-OPN siRNA conjugate. These aptamers were selected as therapeutic leads based on 70–90% OPN inhibition in cancer (GL261, 344SQ, 4T1B2b) and myeloid (DC2.4) cells relative to scramble controls. In established immune competent 344SQ lung cancer and 4T1B2b breast cancer models, these aptamers, including in combination, demonstrate therapeutic activity by inhibiting tumor growth. The Ncl-OPN siRNA aptamer demonstrated efficacy in an immune competent orthotopic glioma model administered systemically secondary to the ability of the aptamer to access the glioma TME. Therapeutic activity was demonstrated using both aptamers in a breast cancer brain metastasis model. Targeted inhibition of OPN in tumor cells and myeloid cells using bifunctional aptamers that are internalized by specific cell types and suppress OPN expression once internalized may have clinical potential in cancer treatment.